A Path-Priority Based Relay Selection Algorithm for VoIP - Hua Qu; Jihong Zhao; Lixia Wang; Shiqi Dong (Dianxin kexue)
When routing the end-to-end path in the overlay network for VoIP service, it is necessary to ensure the path delay less than 150 ms. Due to the triangle inequality variations existed generally in the overlay network, the current research focus on building a multi-path routing using relay node selection algorithms instead of the end-to-end path to guarantee the VoIP service delay requirements. But the existed relay algorithms have limitations, such as deployment difficult, ignoring the difference between the paths. A new algorithm-a path-priority based relay selection algorithm for VoIP was proposed. First, the concept of the path priority degrees was introduced to describe the reference delay and the difference with the default IP path. Then a relay table was built and the best node was selected from the table to route the path. The algorithm reduced the delay further through two-hop relay selection algorithm at last. Simulation results show that the proposed method can reduce the transmission delay of VoIP services and enhance the user experience of VoIP.